Efeitos do treinamento resistido e da ovariectomia sobre marcadores de biogênese mitocondrial e capacidade oxidativa do músculo esquelético de ratas - Barbosa, Marina Rodrigues (Universidade Federal de São Carlos, 2015)
The decrease of regulate the estrogen production that occurs at menopause is typically followed by increase of several deleterious changes in the skeletal muscle system. Menopause is mimicked experimentally by a technique called ovariectomy. The ovariectomy produces increased total body mass, changes in body composition and lipid profile, reduction in skeletal muscle (sarcopenia) and bone mineral mass (osteopenia). Mitochondria play a crucial role in a myriad of cellular processes including oxidative phosphorylation, biosynthetic pathways and programming of cell death. Alteration of mitochondrial biogenesis markers in ovariectomized rats and the effects of resistance training (RT) and estrogen replacement (RE) are unclear. Purpose: This study aimed to investigate the effects of Ovariectomy (Ovx), RT and ER on markers of mitochondrial biogenesis and protein expression related to oxidative capacity in the rat gastrocnemius pool. Methods: ER was performed using Silastic® capsules. During the 12-week RT, the animals climbed a ladder with weights attached to their tails. RT began simultaneously for all experimental groups. Gene expression was analysed by RT-PCR, and protein content was determined by western blotting. Results: The estrogen deficiency associated with Ovx decreased the gene expression of the mitochondrial biogenesis markers PGC-1α (~73%), NRF-1 (~44%), and TFAM (~53%) (p<0.05) and decreased the protein expression of phosphorylated AMPK, CREB and AKT, which are related to oxidative capacity, compared to the Sham-Sed group. RT increased PGC- 1α (~59%) and TFAM (~48%) expression compared to the Ovx-Sed group. The combination of RT and ER was superior to the Ovx-Sed and Ovx-RT treatments regarding the gastrocnemius muscle. Conclusions: This study showed that ovaries removal affects transcription factors that regulate mitochondrial biogenesis in skeletal muscle. According to our results and evidence from the literature, and estradiol levels of exercise appear to play an important role in the protection of mitochondrial dysfunction in skeletal muscle of rats.
Effects of resistance training and ovariectomy on mitochondrial biogenesis and oxidative capacity markers of skeletal muscle of rats
Keywords: Fisiologia; Biogênese mitocondrial; Ovariectomia; Treinamento resistido; Estrógenos; Músculo esquelético; Mitochondrial biogenesis; Ovariectomy; Resistance training; Estrogen replacement; Skeletal muscle; Rats; CIENCIAS BIOLOGICAS::FISIOLOGIA